Latin Americans peoples of the world ; the culture, geographical setting, and historical background of 42 Latin American peoples - Moss, Joyce; Wilson, George (Gale Research, 1989)
An exploration of ethnic groups in Latin America, discussing culture, family structure, dress, nutrition, education, industry, religion, history, population, land, and climate.
Keywords: Ethnologie - Amérique latine; Latijns-Amerikanen; Alltag, Brauchtum; Ethnology -- Latin America; Bevölkerung; Amérique latine - Conditions sociales; Amérique latine - Moeurs et coutumes; Lateinamerika; Latin America -- Social life and customs